1. The problem statement, all variables and given/known data dy/dx=y*e^(x+y) solve for y 3. The attempt at a solution move the y's over to the other side: dy/(y*e^y)=e^x.dx then you integrate and this is where i get screwed up. i use inverse product rule where u=y and v'=e^y, and i also tried u=e^y and v'=y. but this didnt get me anywhere so i did it again for the integral on the right hand side for each and it still didnt get me anywhere. HELP! also, i doubt if id be able to put it back into y= forms so yea could you help with that too? if not it doesnt really matter. primarily its just the integrating i want help with.